Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the roots of the quadratic equation [tex]\(2x^2 - 21x + 27 = 0\)[/tex], we need to solve the factored form of the equation. Given that:
[tex]\[ 2x^2 - 21x + 27 = (2x - 3)(x - 9) = 0 \][/tex]
We need to find the values of [tex]\(x\)[/tex] that make the factored equation equal to zero. This can be done by setting each factor equal to zero and solving for [tex]\(x\)[/tex].
Let's consider each term in the factored form separately:
1. [tex]\(2x - 3 = 0\)[/tex]
2. [tex]\(x - 9 = 0\)[/tex]
### Solving these equations:
1. Solving [tex]\(2x - 3 = 0\)[/tex]:
[tex]\[ 2x - 3 = 0 \][/tex]
Add 3 to both sides:
[tex]\[ 2x = 3 \][/tex]
Now, divide by 2:
[tex]\[ x = \frac{3}{2} \][/tex]
2. Solving [tex]\(x - 9 = 0\)[/tex]:
[tex]\[ x - 9 = 0 \][/tex]
Add 9 to both sides:
[tex]\[ x = 9 \][/tex]
So, the roots of the original quadratic equation are [tex]\(x = \frac{3}{2}\)[/tex] and [tex]\(x = 9\)[/tex].
### Conclusion:
The equations that need to be solved to find these roots are:
- [tex]\(x - 9 = 0\)[/tex]
- [tex]\(2x - 3 = 0\)[/tex]
Thus, the correct answer is:
A. [tex]\(x - 9 = 0\)[/tex]
E. [tex]\(2x - 3 = 0\)[/tex]
[tex]\[ 2x^2 - 21x + 27 = (2x - 3)(x - 9) = 0 \][/tex]
We need to find the values of [tex]\(x\)[/tex] that make the factored equation equal to zero. This can be done by setting each factor equal to zero and solving for [tex]\(x\)[/tex].
Let's consider each term in the factored form separately:
1. [tex]\(2x - 3 = 0\)[/tex]
2. [tex]\(x - 9 = 0\)[/tex]
### Solving these equations:
1. Solving [tex]\(2x - 3 = 0\)[/tex]:
[tex]\[ 2x - 3 = 0 \][/tex]
Add 3 to both sides:
[tex]\[ 2x = 3 \][/tex]
Now, divide by 2:
[tex]\[ x = \frac{3}{2} \][/tex]
2. Solving [tex]\(x - 9 = 0\)[/tex]:
[tex]\[ x - 9 = 0 \][/tex]
Add 9 to both sides:
[tex]\[ x = 9 \][/tex]
So, the roots of the original quadratic equation are [tex]\(x = \frac{3}{2}\)[/tex] and [tex]\(x = 9\)[/tex].
### Conclusion:
The equations that need to be solved to find these roots are:
- [tex]\(x - 9 = 0\)[/tex]
- [tex]\(2x - 3 = 0\)[/tex]
Thus, the correct answer is:
A. [tex]\(x - 9 = 0\)[/tex]
E. [tex]\(2x - 3 = 0\)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.